2009
DOI: 10.1002/nbm.1391
|View full text |Cite
|
Sign up to set email alerts
|

A multi‐compartmental SE‐BOLD interpretation for stimulus‐related signal changes in diffusion‐weighted functional MRI

Abstract: A new interpretation is proposed for stimulus-induced signal changes in diffusion-weighted functional MRI. T(2)-weighted spin-echo echo-planar images were acquired at different diffusion-weightings while visual stimulation was presented to human volunteers. The amplitudes of the positive stimulus-correlated response and post-stimulus undershoot (PSU) in the functional time-courses were found to follow different trends as a function of b-value. Data were analysed using a three-compartment signal model, with one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 41 publications
1
16
1
Order By: Relevance
“…For instance, a study showed decreased apparent diffusion coefficient, implying increased normalized signal intensity for about 1.57% with b-value of 1443-1461 mm 2 /s and this result was consistent with our result that the normalized signal intensities increased for about 2.17% with b-value of 1400 mm 2 /s, Δ of 30 ms, and r of 10.1 μm [1]. In other studies, 1-2% increases of the raw signal intensities with the b-value of 1600-1800 mm 2 /s were reported [2], [3], [5]. In our simulations, we obtained 2.15-2.18% increases in the normalized signal intensities with the b-value of 1600-1800 mm 2 /s, Δ of 30 ms, and r of 10.1 μm.…”
Section: Discussionsupporting
confidence: 93%
“…For instance, a study showed decreased apparent diffusion coefficient, implying increased normalized signal intensity for about 1.57% with b-value of 1443-1461 mm 2 /s and this result was consistent with our result that the normalized signal intensities increased for about 2.17% with b-value of 1400 mm 2 /s, Δ of 30 ms, and r of 10.1 μm [1]. In other studies, 1-2% increases of the raw signal intensities with the b-value of 1600-1800 mm 2 /s were reported [2], [3], [5]. In our simulations, we obtained 2.15-2.18% increases in the normalized signal intensities with the b-value of 1600-1800 mm 2 /s, Δ of 30 ms, and r of 10.1 μm.…”
Section: Discussionsupporting
confidence: 93%
“…During activation, they hypothesize that the compartment with slower diffusion increases (because of cell swelling), causing the overall diffusion to decrease and the signal to therefore increase. However, a similar effect could arise for compartments with fixed volume (no swelling) that had different diffusion coefficients and T 2 values (40). As the b value changes, the signal contribution of the T 2 BOLD effect in each compartment would be determined by its diffusion coefficient, and the percent signal change would therefore depend on b value.…”
Section: Discussionmentioning
confidence: 94%
“…Also, our model simplifies the diffusion properties of water in brain matter, which cannot be described assuming isotropic diffusion characterized by a single diffusion coefficient (40). In a very recent study, Kershaw et al (11) explained their findings in DFMRI experiments by means of a model that considers a slow-and a fast-diffusing pool, indicating that the diffusion characteristics could be crucial to explain DFRMI findings.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, one can safely assume that it is exclusively caused by the interaction between diffusion weighting gradients and background gradients. In the study by Fujita (41), a scaling law, b ¼ DÁTE/r 2 , was derived that allows a set of results calculated for a specific diffusion constant (D) and vessel radius (r) to be applied to a situation with the same b but different D and r. Noting that the largest extravascular SE-BOLD signal changes occur when b lies between 2 and 4, it is possible to estimate the range of vessel sizes that are most sensitive for molecules diffusing with a specific diffusion coefficient (11). Our results suggest that this range also depends on the size of the bvalue if a sequence is chosen that does not minimize cross-terms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation